Financial Sustainability and Poverty Outreach: The Case of Microfinance Institutions in Eastern Europe and Central Asia. Issue 1 (January 2017) - Sheremenko, Ganna; Escalante, Cesar L; Florkowski, Wojciech J
Abstract The collapse of state ownership, following the dissolution of the Soviet Union, launched a new era of self-employment and small businesses in need of financing services throughout the region. This research investigates whether the traditional microfinance lending paradigm that adopts a two-pronged mission of financial sustainability and poverty outreach applies to young commercialized microfinance institutions in Eastern Europe and Central Asia. The analysis employs a residual standard error approach to ordinary least squares and 2-stage least squares estimation, as well as recursive model estimation. The results suggest that financial sustainability can be adversely affected when interest rates exceed a threshold of 80 per cent and an individualized instead of group lending approach is adopted. However, poverty outreach is improved by servicing small loans to more borrowers, particularly women. Abstract L'effondrement de la propriété de l'Etat, après la dissolution de l'Union Soviétique, a lancé une nouvelle ère de travail indépendant et des petits business nécessitant des services de financement à travers la région. Cette recherche a pour but d'enquêter afin de savoir si le paradigme d'emprunt de la microfinance traditionnelle, qui adopte une double mission de viabilité financière et de vulgarisation de la pauvreté, s'applique aux jeunes institutions dans la branche de la microfinance commercialisée en Europe de l'Est et en Asie Centrale. L'analyse fait recours à une approche erreur résiduelle standard (ERS) pour la méthode des moindres carrés ordinaires (MCO) et à une estimation de la méthode des doubles moindres carrés ainsi qu'une estimation du modèle séquentiel. Les résultats suggèrent que la viabilité financière peut être défavorablement affectée lorsque les taux d'intérêt excèdent un seuil de 80% et qu'un recours à une approche d'emprunt individuelle plutôt que de groupe est adoptée. D'autre part, la vulgarisation de la pauvreté est améliorée en assurant le service des petits emprunts à plus d'emprunteurs, plus particulièrement aux femmes.